Formulasi dan Evaluasi Tablet Effervescent dari Ekstrak Buah Tampoi (Baccaurea macrocarpa): Formulation and Evaluation of Effervescent Tablets from Tampoi Fruits Exstract (Baccaurea macrocarpa) - Haryono, Ika Avrilina; Noval, Noval (Jurnal Surya Medika (JSM), 2022)
Tampoi is one of the many plants found in East Kalimantan, has secondary metabolic content in the form of saponins, flavonoids, and alkaloids, and has antioxidant activity. The antioxidants produced by the human body are not sufficient to fight free radicals, therefore the body requires the intake of antioxidants from the outside, so to help increase public interest in consumption, researchers are interested in making preparations in the form of extracts and formulated as effervescent tablets from tampoi fruit extract which are useful as antioxidants and increase immunity. The purpose of this study was to determine a good formula for making effervescent tablets from tampoi fruit extract with variations of PVP K30 as a binder. Making tablets using direct compression method with an evaluation of effervescent powder including the angle of repose test, flow rate, setting, compressibility, and moisture of the powder. Evaluation of effervescent tablets included organoleptic test, weight uniformity test, tablet friability test, tablet hardness test, and tablet dissolving time test. The results obtained in the evaluation of the effervescent powder, the angle of repose test has met the requirements, while the test for flow velocity, sizing, compressibility, and moisture of the powder has not met the requirements. The results of the physical evaluation of the tablet weight uniformity test on F1 and F2 were in accordance with the requirements, the tablet friability test on F3 and F4 had met the requirements, the F3 tablet hardness test had met the requirements, and the tablet dissolving time test resulted that all formulas met the requirements with the best formula namely F1 which has the fastest tablet dissolution time. The conclusion of the study from the evaluation of the dissolving time which is the main parameter of the effervescent tablet preparation of tampoi fruit extract, the best formula was obtained, namely F1 with a PVP K30 concentration of 0.5 mg resulting in a tablet dissolving time of 01.99 minutes.